Household Consumption When the Marriage Is Stable - Laurens Cherchye; Thomas Demuynck; Bram De Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2014)
We develop a novel framework to analyze the structural implications of the marriage market for household consumption patterns. We start by defining a revealed preference characterization of efficient household consumption when the marriage is stable. In particular, stability means that the marriage matching is individually rational and has no blocking pairs. We show that this revealed preference characterization generates testable conditions even if there is only a single consumption observation per household and individual preferences are heterogeneous across households. In addition, the characterization allows for identifying the intrahousehold decision structure (including the sharing rule) under the same minimalistic assumptions. An application to Dutch household data demonstrates the empirical usefulness of our theoretical results.
Keywords: C14; D11; C78; 330; marriage market; stable matching; Pareto efficient household consumption; testable implications; sharing rule identification; preference heterogeneity